Urban governance and policy mixes for nature-based solutions and integrated water policy. Issue 5 (3rd September 2022) - Kirsop-Taylor, Nick; Russel, Duncan; Jensen, Anne
ABSTRACT: This paper explores how varied systems of governance work at the European city level to deliver different policy mixes for implementing nature-based approaches which support integrated water management and policy. Urban systems provide unique insights here due to the concentration of consumption, economic activities and excessive land-use pressures. However, few studies are providing generic insights, rooted in policy and political theory perspectives, on the dynamic impact of urban governance systems on different mixes of policies to integrate urban nature and water management approaches. The paper fills this gap through an extensive literature review. It first draws on analysis that focuses on institutional logics of operation to understand how urban institutional arrangements of governance shape the framing of the policy problem and how this influences the choice of policy approaches. It then explores the related administrative processes including decision support tools, participatory approaches, and funding regimes. These administrative approaches deliver, potentially, different policy responses that take into account integrated nature-based policy approaches to urban water governance.